Communicating Beyond Barriers: Indonesian Cultural Perspectives on Deafness in The Silent Child (2017) Short Film - Pratiwi, Cysakaren Diva; Meyrasyawati, Dewi (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 1 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
This study explores how Indonesian students interpret the portrayal of deafness and communication in The Silent Child (2017) using Stuart Hall’s Encoding/Decoding Theory. Hall’s model emphasizes that media messages are encoded with a preferred meaning but are actively interpreted by audiences based on their cultural background and experiences. Through a qualitative approach, this research analyzes audience responses from eight students at Rumah Bahasa Surabaya to examine their reception of the film’s themes on inclusive education and sign language. Findings suggest that while most students aligned with the film’s dominant-hegemonic position, recognizing sign language as essential for deaf individuals, some engaged in negotiated readings, questioning its applicability to Indonesia’s oralism-dominated education system. A minority exhibited oppositional readings, resisting the film’s perspective based on personal beliefs about communication and disability. The study also examines cultural transfer, illustrating how local norms influence the interpretation of global narratives. Additionally, the role of non-verbal communication and emotional engagement in fostering empathy was examined, revealing that silence and visual storytelling deepened audience connections to the protagonist. While the film successfully raised awareness, motivation to take action, such as learning sign language, varied among participants. These findings highlight the complexity of cross-cultural media reception and contribute to discussions on inclusive education, disability representation, and audience engagement. By applying Hall’s framework, this study underscores how films serve as sites of cultural negotiation, influencing audience perceptions through both global and local ideological lenses.